2018
DOI: 10.1111/nph.15218
|View full text |Cite
|
Sign up to set email alerts
|

Ericoid mycorrhizal fungi and their genomes: another side to the mycorrhizal symbiosis?

Abstract: Contents Summary1141I.Introduction1141II.The ericoid mycorrhizal lifestyle1141III.Lessons from the mycorrhizal fungal genomes1142IV.ERM fungi: a discordant voice in the mycorrhizal choir1143V.An endophytic niche for ERM fungi1144VI.Specialised vs unspecialised mycorrhizal fungi?1145VII.Conclusions and perspectives1145Acknowledgements1146References1146 Summary The genome of an organism bears the signature of its lifestyle, and organisms with similar life strategies are expected to share common genomic traits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 54 publications
(102 reference statements)
2
47
0
1
Order By: Relevance
“…We concluded that, in contrast to arbuscular mycorrhizal fungi, ericoid fungi produce cell-wall-degrading enzymes and that this capacity was probably modulated during the interaction with host and nonhost plants (Perotto et al, 1995). Indeed, genomics and transcriptomics of arbuscular mycorrhizal fungi (Tisserant et al, 2013;Salvioli et al, 2016;Chen et al, 2018) and of ericoid fungi (Kohler et al, 2015;Martino et al, 2018;Perotto et al, 2018) have demonstrated that arbuscular mycorrhizal fungi do not possess genes coding for cell-wall-degrading enzymes, in contrast to ericoid fungi, largely confirming the hypotheses advanced about 25 years before! In the absence of molecular data, ultrastructural observations have allowed researchers to look beyond the hedge: the deep reorganization of the cortical cells following the fungal colonization suggested a reprogramming of the molecular plant machinery that has been largely confirmed by RNA-sequencing studies in all the mycorrhizal symbioses (Veneault-Fourrey et al, 2014;Fiorilli et al, 2015;Peter et al, 2016;Fochi et al, 2017;Sugimura & Saito, 2017;Martino et al, 2018).…”
Section: The Colonization Process: How Cellular Studies Predicted supporting
confidence: 71%
See 1 more Smart Citation
“…We concluded that, in contrast to arbuscular mycorrhizal fungi, ericoid fungi produce cell-wall-degrading enzymes and that this capacity was probably modulated during the interaction with host and nonhost plants (Perotto et al, 1995). Indeed, genomics and transcriptomics of arbuscular mycorrhizal fungi (Tisserant et al, 2013;Salvioli et al, 2016;Chen et al, 2018) and of ericoid fungi (Kohler et al, 2015;Martino et al, 2018;Perotto et al, 2018) have demonstrated that arbuscular mycorrhizal fungi do not possess genes coding for cell-wall-degrading enzymes, in contrast to ericoid fungi, largely confirming the hypotheses advanced about 25 years before! In the absence of molecular data, ultrastructural observations have allowed researchers to look beyond the hedge: the deep reorganization of the cortical cells following the fungal colonization suggested a reprogramming of the molecular plant machinery that has been largely confirmed by RNA-sequencing studies in all the mycorrhizal symbioses (Veneault-Fourrey et al, 2014;Fiorilli et al, 2015;Peter et al, 2016;Fochi et al, 2017;Sugimura & Saito, 2017;Martino et al, 2018).…”
Section: The Colonization Process: How Cellular Studies Predicted supporting
confidence: 71%
“…We concluded that, in contrast to arbuscular mycorrhizal fungi, ericoid fungi produce cell‐wall‐degrading enzymes and that this capacity was probably modulated during the interaction with host and nonhost plants (Perotto et al ., ). Indeed, genomics and transcriptomics of arbuscular mycorrhizal fungi (Tisserant et al ., ; Salvioli et al ., ; Chen et al ., ) and of ericoid fungi (Kohler et al ., ; Martino et al ., ; Perotto et al ., ) have demonstrated that arbuscular mycorrhizal fungi do not possess genes coding for cell‐wall‐degrading enzymes, in contrast to ericoid fungi, largely confirming the hypotheses advanced about 25 years before!…”
Section: The Colonization Process: How Cellular Studies Predicted Futsupporting
confidence: 57%
“…Most importantly they also form a mutualistic association with ericoid mycorrhizal fungi that is crucial to access soil nutrients otherwise unavailable for plant uptake. Ericoid mycorrhizal fungi retained more genes involved in the decomposition of lignocellulose during their evolution than ectomycorrhizal fungi (Kohler et al ., 2015; Perotto et al ., 2018), allowing them to decompose a wide range of complex and recalcitrant organic substrates. Despite their importance, little is known about the diversity of ericoid mycorrhizal fungi and the ecological factors that shape species diversity and community structure (Leopold, 2016; Kohout, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Critical in this endeavor will be the use of genomic information on the recently sequenced mycorrhizal fungi (Kohler et al ., ; Martino et al ., ; Chen et al ., , pp. 1161–1171; see also Perotto et al ., , pp. 1141–1147).…”
Section: Mycorrhizal Fungal Community Ecologymentioning
confidence: 99%